Securitization and Authoritarianism The AKP's Oppression of Dissident Groups in Turkey - Yilmaz, Ihsan; Shipoli, Erdoan; Demir, Mustafa (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book focuses on securitization and authoritarianism in Turkey with research on the country's Islamist populist ruling party's (AKP) oppression of different socio-political, ethnic and religious groups. In doing so, it analyzes how the AKP has securitized to oppress different socio-political groups and identities, according to the time and need for the party's political survival. Research in the book sheds light on the use of traumas, conspiracy theories, and fear as tools in the securitization and repression processes. Ihsan Yilmaz is Research Professor and Chair of Islamic Studies at the Alfred Deakin Institute for Citizenship and Globalisation (ADI), Deakin University, Melbourne, Australia. Erdoan Shipoli is a Visiting Scholar at the Center for Muslim-Christian Understanding in the Edmund A. Walsh School of Foreign Service at Georgetown University, Washington DC, USA. Mustafa Demir is a lecturer at the Department of Politics, Faculty of Arts and Social Sciences, University of Surrey, England, UK.
Chapter 1: Introduction -- Chapter 2: Securitisation Theory -- Chapter 3: Turkish Securitisation Culture -- Chapter 4: Kemalists, White Turks, Leftists -- Chapter 5: Securitisation of Islamic Groups And Parties -- Chapter 6: Securitisation of The Kurds -- Chapter 7: Securitisation of The Alevis -- Chapter 8: Fruits Of Securitisation. .
Keywords: Comparative government; Human rights; Identity politics; Comparative Politics; Politics and Human Rights; Identity Politics